METODE PENDIDIKAN AKHLAK - Muhrin, Muhrin (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
Discussion of the issue of moral education is the same as discussion of the aims of education, because several expert opinions say that the aim of education is moral education. Some experts say that morals do not need to be formed, because morals are instincts that humans are born with. Morals are the result of education, training, coaching and hard and serious struggle. As in the opinion of Ibn Miskawaih, Ibn Sina, and Imam al-Ghazali. In reality, in society, moral education efforts to shape children's character through various educational institutions with various methods continue to be developed so that moral education can adapt to children's talents, interests and development and is relevant to current technological developments.